Oliver : the second-largest living thing on Earth - Crute, Josh (Page Street Kids, an imprint of Page Street Publishing Co., 2018)
Oliver wishes he were as popular and important as Sherman, the largest giant sequoia tree, until he discovers it is enough to be part of something big.